The complex biology and contribution of Staphylococcus aureus in atopic dermatitis, current and future therapies. (11th June 2017) - Hepburn, L.; Hijnen, D.J.; Sellman, B.R.; Mustelin, T.; Sleeman, M.A.; May, R.D.; Strickland, I.
Abstract : What's already known about this topic? Staphylococcus aureus infections are closely associated with disease exacerbation in patients with atopic dermatitis. Antibiotic‐resistant strains are becoming more commonplace and there is a need for the development of new drugs. What does this study add? New therapeutic approaches using monoclonal antibodies are being developed to help combat S. aureus infections. These new therapies specifically target the infecting pathogen and do not harm the beneficial microbiome or cause resistance to antibiotics. Summary: Atopic dermatitis (AD) is a complex, chronic inflammatory skin disorder affecting more than 10% of U.K. children and is a major cause of occupation‐related disability. A subset of patients, particularly those with severe AD, are persistently colonized with Staphylococcus aureus and exacerbation of disease is commonly associated with this bacterium by virtue of increased inflammation and allergic sensitization, aggravated by skin barrier defects. Understanding the complex biology of S. aureus is an important factor when developing new drugs to combat infection. Staphylococcus aureus generates exoproteins that enable invasion and dissemination within the host skin but can also damage the skin and activate the host immune system. Antibiotics are often used by dermatologists to aid clearance of S. aureus ; however, these are becoming less effective and chronic usage is discouraged with the emergence of multiple antibiotic‐resistant strains. New ways to target S. aureus using monoclonal antibodies and vaccines are now being developed. This review will attempt to evaluate the key biology of S. aureus, current treatment of S. aureus infections in AD and recent advances in developing new anti‐ S. aureus therapies that have potential in severe AD.